PROLANIS PROGRAM (DIET, MEDICATION, AND PHYSICAL ACTIVITY) ON GLYCEMIC CONTROL OF TYPE 2 DM PATIENTS IN MAKASSAR CITY - Sheinni Paradise1*, M. Alimin Maidin1, Amran Razak2, Abdul Rahman Kadir3, (Chelonian Research Foundation, 2024)
Background: Blood sugar levels in people with diabetes can be controlled by managing a healthy diet and doing physical exercise. Diabetes mellitus treatment is one of the treatments included in the National Health Insurance (JKN) program in Indonesia. In the JKN era, the Diabetes Mellitus type 2 Chronic Disease Management Program was made one of the programs of the BPJS which was renamed the Program Pengelolaan Penyakit Kronis (Prolanis). Aim: Knowing prolanis program (diet, medication, and physical activity) on glycemic control of type-2 DM patients Method: The study was conducted in November 2023-Januari 2024 at Puskesmas Kassi-Kassi and Puskesmas Kalukubodoa. The number of samples at Puskesmas Kassi-Kassi was 183 people, and Puskesmas Kalukubodoa was 168 people with a total sample of 351 people with quantitative research methods using questionnaires. Results: Based on the results of research conducted on 351 respondents, it can be explained that there were more respondents with a good diet, namely (92.6%), taking medicine according to doctor's recommendations, namely (91.2%). Respondents with moderate physical activity were (92.6%), and respondents with controlled glycemic control were more, namely (93.7%). The statistical test results obtained each p value = 0.000, this means that there is an effect of diet, medication, and physical activity (gymnastics) on the glycemic control of patients with type-2 diabetes. Conclusion: In the prolanis program, there is an effect of diet, medication, and physical activity (gymnastics) on the glycemic control of type-2 DM patients in Makassar City. Keywords: Diet, Medication, Physical Activity (Gymnastics), Glycemic Control, Type-2 DM